Nitrogen doping of amorphous carbon thin film prepared by camphor using thermal CVD / Arina Yusof - Yusof, Arina (2010)
This research investigates on the nitrogen doping of amorphous carbon thin film that have been prepared by camphor using thermal CVD method at different temperature. This research used argon (Ar), camphor oil and nitrogen (N) as carrier source and dopant gases, respectively. The effect of nitrogen doping of the amorphous carbon thin film on electrical and optical properties were characterized by using Current-Voltage (I-V) measurement and UV-VIS-NIR spectroscopy. The I-V measurement studies demonstrate that the current measured for sample that have been deposited at higher temperature gives more conductivity. Optical band gap for the undoped thin film is about 0.1 to 0.4 eV. This study also shows that the optical band gap (Eg) for doped thin film decreased from 0.5 to 0.1 eV when the deposition temperature is increased.